Voice of the Wildcats : Claude Sullivan and the Rise of Modern Sportscasting - Sullivan, Alan (Book collections on Project MUSE., 2014)
As one of the first voices of the University of Kentucky men''s basketball program, Claude Sullivan (1924--1967) became a nationally known sportscasting pioneer. His career followed Kentucky''s rise to prominence as he announced the first four NCAA championship titles under Coach Adolph Rupp and covered scrimmages during the canceled 1952--1953 season following the NCAA sanctions scandal. Sullivan also revolutionized the coverage of the UK football program with the introduction of a coach''s show with Bear Bryant -- a national first that gained significant attention and later became a staple a.